BRIDGING PHILOLOGY AND MODERN ENGLISH EDUCATION: A PATH TOWARD CRITICAL LANGUAGE AWARENESS - Jumayev Ashurali Eshkeldi o‘g‘li (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This article explores the intersection between traditional philology and contemporary English education, emphasizing how historical and comparative language study can enhance learners' critical thinking, linguistic competence, and cultural awareness. It argues for an integrated approach that values etymology, textual analysis, and language evolution as tools for deeper engagement with English as both a historical and a living language.